Effect of increased greenhouse gas concentration on mean, extreme, and timing of precipitation over Arizona (USA). (30th November 2021) - Georgescu, Matei; Broadbent, Ashley Mark; Balling, Robert C.
Abstract: We use a combination of a regional climate model (RCM) and a global climate model (GCM) to explore potential changes to the complex precipitation regime in the semi‐arid and arid state of Arizona in the American Southwest. The RCM output for the contemporary period (2000–2009) compares well with a gridded precipitation dataset with respect to seasonality, amount, intensity, and diurnal patterns. Output from the GCM forced by the continued buildup of greenhouse gases was dynamically downscaled by the RCM for the period 2090–2099. Results indicate an increase in winter precipitation of 1–2 mm day −1 in the mountainous areas of the state with somewhat smaller increases for the summer and fall seasons; negligible changes were projected for spring precipitation. Extreme precipitation is projected to increase across much of the state in winter (10–30 mm day −1 ) and to a lesser extent in spring. Our results indicate an increase in the 99th percentile of winter season precipitation. However, we note there is substantial seasonal dependency: statewide‐averaged winter season precipitation is projected to undergo greater frequency of wet than dry extreme events, whereas the statewide‐averaged summer, fall, and spring seasons, broadly demonstrate an equal likelihood of increased and decreased extreme precipitation. While the RCM captured the unusual observed night‐time maximum in summer rainfall in the centre of the state, our results do not indicate any change in the diurnal character or sub‐diurnal duration (6–18 hr) of precipitation over the next 100 years. Abstract : We use a combination of a regional climate model and a global climate model to characterize changes to the precipitation regime in the state of Arizona in the American Southwest. Our results indicate an increase in end of century winter precipitation of 1–2 mm day −1, an increase in the 99th percentile of precipitation with substantial seasonal dependency, and no changes in the diurnal character of precipitation over the next 100 years.